The effect of cinnamomum verum and clinacanthus nutans aqueous extract on dehydroepiandrosteron induced polycystic ovarian syndrome (PCOS) in rat - Ahmad, Nur Fatihah (2022)
Polycystic ovarian syndrome is a major disorder characterised by elevated levels of androgens, acne and hirsutism. Current treatment includes metformin which is only effective against PCOS symptoms without treating the underlying cause. In addition, metformin causes significant side effects such as gastrointestinal symptoms, weight gain and increased insulin resistance. The objective of this study was to evaluate the effect of Cinnamomum verum (CV) and Clinacanthus nutans (CN) aqueous extract in PCOS induced rats. Preliminary study for PCOS induction using dosage 6mg/100g/0.2ml of dehydroepiandrosterone (DHEA) in 21 day duration was conducted in these three groups of rats: (a) control group, (b) vehicle only group, and (c) DHEA + vehicle group; to ensure the establishment of PCOS characteristics in the rat model used before proceed to the main study. Thirty female SD rats were divided into six groups of five animals each namely control group, DHEA group, CV group (500mg/kg), CV group (1000mg/kg), CN group (500mg/kg) and CN group (1000mg/kg). CV and CN aqueous extract treatment were continued for 28 days postinduction after induction of PCOS. After treatment completion, all rats were sacrificed. Analysis of hormones, body weight, histopathology and toxicology study of the ovary, liver, uterus and kidney were carried out. In DHEA group, testosterone levels increased significantly compared to non-induced normal rats (p=0.0402) (p<0.05) which reduced to significant level when both extracts were given. Induction of PCOS in rats lead to significant increase in follicular cyst (p<0.0001) and decrease in corpus luteum compared to the control group (p<0.0001). When treatments were given to the PCOS group, there was a significant increase in the number of corpus luteum in both CV extracts (p=0.0002, p=0.0070). Interestingly, the number of follicular cysts also decreased significantly in all CV and CN group (p=<0.001, p=<0.001, p=<0.001, p=<0.001). CN treated rats showed normal morphological organ structure showing non-toxic effect of both plants. However, CV extracts induced mild degenerative changes in liver and kidney at 500mg/kg and 1000mg/kg. In conclusion CV and CN is able to reduce PCOS charasteristics in induced rats model. This study act as a basic for further study on the mechanism of both plants in the treatment of PCOS.